The Involvement of Artificial Intelligence in Addressing Elderly Social Interaction - Noachbriantte Zwezda Sutomo; Mita Purbasari Wahidiyat (Indonesian Journal of Visual Culture, Design, and Cinema, 2025)
Social isolation and loneliness among the elderly have become significant global issues, negatively impacting their mental and physical health. With the advancement of technology and the emergence of artificial intelligence (AI) systems, various potential solutions can be utilized to address these challenges. This study explores the possible involvement of AI in enhancing elderly social interactions, focusing on technologies that help them stay connected with family, friends, and their social environment. This research employs a qualitative approach, including a literature analysis of AI applications that can support elderly social interaction. The findings reveal that AI systems such as social robots, virtual assistants, and chatbot applications hold great potential in reducing loneliness and increasing social connectivity among the elderly. These technologies not only facilitate more frequent social interactions but also provide emotional and cognitive support, ultimately improving their quality of life. Although AI systems offer numerous benefits, challenges such as dependence on technology, initial resistance from the elderly, and limitations in non-verbal communication remain obstacles that need to be addressed. This study concludes that AI involvement in supporting elderly social interactions has great potential. However, its implementation must consider accessibility, comfort, and proper training to ensure its effectiveness in reducing social isolation.